2017
DOI: 10.1017/s0025315417000406
|View full text |Cite
|
Sign up to set email alerts
|

Marine mammal sightings around oil and gas installations in the central North Sea

Abstract: Relatively little is known about the distribution and diversity of marine mammals around offshore anthropogenic structures. We present results obtained from incidental sightings of marine mammals around oil and gas installations located 200 km off the Danish coast. A total of 131 sightings corresponding to about 288 animals were reported between May 2013 and May 2016. A total of seven marine mammal species were identified, five cetaceans: harbour porpoise (Phocoena phocoena), minke whale (Balaenoptera acutoros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Previous acoustic and surface-based visual studies that have detected marine mammals around O&G structures (e.g., Cremer et al, 2009;Todd et al, 2009Todd et al, , 2016Thompson et al, 2010;Delefosse et al, 2018), have now been corroborated by the commercial subsea imagery in this study. Presence of other megafauna species such as sharks (Haugen and Papastamatiou, 2019), rays, and turtles (McLean et al, 2017(McLean et al, , 2019b confirm that marine mammals are not unique in their exploitation of resources on/around anthropogenic structures.…”
Section: Structure Associationsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous acoustic and surface-based visual studies that have detected marine mammals around O&G structures (e.g., Cremer et al, 2009;Todd et al, 2009Todd et al, , 2016Thompson et al, 2010;Delefosse et al, 2018), have now been corroborated by the commercial subsea imagery in this study. Presence of other megafauna species such as sharks (Haugen and Papastamatiou, 2019), rays, and turtles (McLean et al, 2017(McLean et al, , 2019b confirm that marine mammals are not unique in their exploitation of resources on/around anthropogenic structures.…”
Section: Structure Associationsupporting
confidence: 78%
“…Another North and Irish Sea acoustic and visual study on various offshore O&G installations, reported multiple marine mammal species, including harbor porpoise, Atlantic white-sided (Lagenorhynchus acutus), white-beaked (Lagenorhynchus albirostris), and common (Delphinus delphis) dolphin, minke whale (Balaenoptera acutorostrata), and both common (Phoca vitulina) and gray (Halichoerus grypus) seal (Todd et al, 2016). Similarly, Delefosse et al (2018) analyzed visual sightings from 25 O&G installations in the Dutch sector of the North Sea, recording 131 sightings of 288 individual marine mammals over a 3-year period. Harbor porpoise was the most commonly sighted species (41% of sightings), followed by minke whale (31%).…”
Section: Introductionmentioning
confidence: 99%
“…Still, even considering these caveats, the data collected during the non-systematic surveys enable the construction of a positively identified species list and a first indication of the cetacean population status and density. The applied method provides a low-cost approach to obtain valuable long-term information for areas with limited or no specific monitoring effort over a wide geographic area (Delefosse et al, 2018). Although interpretation of nonsystematically collected data is difficult without measure of effort (Evans and Hammond, 2004), with stringent data filtering and quality control, valuable information can be obtained (Pikesley et al, 2012).…”
Section: Caveatsmentioning
confidence: 99%
“…Advocates argue that the rigs mimic the stone reefs that were once more prevalent in the North Sea and provide the hard substrate needed for blue mussels and corals to colonize (A. M. Jørgensen, 2018;Pearce, 2018;Sonne, 2018). Proponents refer to the research on their mimicry of natural structures (Henry, Harries, Kingston, & Roberts, 2017), enhanced productivity (Claisse et al, 2014;Fowler et al, 2018), marine mammal attraction (Delefosse, Rahbek, Roesen, & Clausen, 2018), and growing scientific consensus on revising artificial reef guidelines in OSPAR (Fowler et al, 2018).…”
Section: The Oasis In the Desert Storylinementioning
confidence: 99%